Faktor Resiko Ergonomi dengan Quick Exposure Check pada Pekerja Batik Tulis Berkah Lestari, Bantul, Yogyakarta - Ratih Pramitasari; Eko Hartini (Dian Nuswantoro Semarang, 2018)
Based on Indonesian Statistic Center, in 2012 total of textile industry (including batik) was 4,553 businesses. The process of making traditional batik is still through a manual process which are draw the pattern in fabric, cover the pattern using hot candle, coloring the fabric and removing the candle from fabric. The work attitude of batik workers is to sit in a small chairs without backrest and do batik activities for proximately 6 hours/day. This research is a quantitative study using a cross sectional research design. The method used is observation to observe the work posture of workers when doing work and using the QEC (Quick Exposure Check) quetionnaire to assess work attitudes. The study population was batik workers in Bantul, Yogyakarta with a sampling technique using simple random sampling totaling 50 workers. Based on the assessment of the level of exposure to ergonomic risk using Quick Exposure Check, work attitudes in batik workers have a very high score on the neck with a percentage of 8%. Followed by 34% and 44% with high and medium exposure levels. The working attitude on the back of the batik is also considered to have a high exposure level with a percentage of 4% and a moderate exposure rate of 68%. The work position of batik workers in around their wrist, has a moderate score with a percentage of 74%. Unlike other body parts, the work attitude of the batik does not overload the batik shoulder which has a low score of 62%. Workers who complained of difficulties in doing work were also quite high with a percentage of 66%, relatively low scores on driving work attitudes, exposure to vibration and work stress. Based on these data, it is known that the most risky work attitudes to workers in batik are on the both upper neck and bottom neck. From the results of this study can be made interventions to reduce the risk of exposure to work attitudes on the neck of batik workers, Bantul, Yogyakarta.